Unplugging beyond the workplace: A scoping review of non-work digital detox strategies - Ema Štánerová; Eva Rošková; Milica Schraggeová; Nina Urukovičová; Jozef Smoroň (Social Sciences and Humanities Open, 2025)
Background: The pervasive use of information and communication technologies (ICTs) has extended into personal time, making it difficult for working adults to disconnect beyond their professional responsibilities. Digital detox, defined as the intentional break from ICTs, serves as a potential solution to counteract the constant connectivity. However, non-work digital detox strategies, understood as methods and activities deliberately performed outside work settings to reduce ICT use, remain underexplored. To date, existing research lacks a comprehensive review and classification of these strategies, particularly in a way that distinguishes between methods (practices enabling disconnection) and activities (alternative engagements during detox). Objective: This scoping review aimed to map and categorize existing non-work digital detox strategies for working adults. Specifically, it sought to answer the following research questions: (1) What methods are used for non-work digital detox among working adults? (2) What alternative activities are practiced during these detox periods? Methods: This scoping review adhered to PRISMA-ScR guidelines. Studies were systematically searched in PubMed, Scopus, and Web of Science up to August 12, 2024. Eligible studies examined digital detox methods and/or activities suitable for adults in a working population, specifically those applicable outside the workplace. Two independent researchers screened abstracts, reviewed full texts, extracted data, and assessed methodological quality. Results: A total of 12 studies, comprising 3040 participants, were included, spanning the years 2019–2024. Six categories of detox methods (e.g., device restriction and app control) and seven categories of activities (e.g., physical and social activities) were identified. The heterogeneity of study designs and measured outcomes precluded a definitive evaluation of the effectiveness of these strategies. Conclusion: The findings provide a structured framework for digital detox interventions, allowing for the individualized combination of methods and activities. Future research should prioritize evaluating the effectiveness of these strategies using standardized designs and outcomes to enhance their applicability and evidence base.